Criminal Law Reform to Increase the Effectiveness of the Justice System in Overcoming Crime - Kesuma, Derry Angling (GoAcademica Research & Publishing, 2024)
This study explores the imperative need for comprehensive criminal law reform to enhance the efficacy of the justice system in combating crime. As societies evolve, so do the complexities of criminal activities, necessitating a reevaluation of legal frameworks to address emerging challenges. The current legal landscape often proves inadequate in addressing the dynamic nature of criminal behavior, resulting in inefficiencies in crime prevention, investigation, and prosecution. The research investigates key areas of reform, including the modernization of outdated statutes, the incorporation of advanced technologies in crime detection and evidence gathering, and the implementation of evidence-based sentencing practices. By examining successful models from jurisdictions that have already undergone significant legal reforms, this study aims to identify best practices that can be adapted and integrated into existing legal systems. Furthermore, the research considers the socio-economic factors influencing criminal behavior, advocating for a holistic approach that combines legal reforms with social interventions. Such an approach seeks to address root causes of criminality, offering a more sustainable and effective strategy for crime reduction. Through a comprehensive analysis of existing legal frameworks, case studies, and sociological data, this study contributes valuable insights to the ongoing discourse on criminal justice reform. The findings aim to inform policymakers, legal practitioners, and the public, fostering a nuanced understanding of the multifaceted challenges associated with contemporary crime and the necessary steps for a more effective and equitable justice system.